When Vegans Are Monstrous: Review of Emelia Quinn, Reading Veganism: The Monstrous Vegan, 1818 to Present - Elliott, Alba S. (Humanimalia, 2023)
Emelia Quinn, Reading Veganism: The Monstrous Vegan, 1818 to Present. Oxford English Monographs. Oxford: Oxford University Press, 2021. ix, 188 pp. £65.00 (hb).